Spinal and articular disorders prevention concept for elite sports - Rodichkin, P. V.; Shalamanov, N. S.; Buznik, G. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes an idea of universal spinal and articular disorders prevention concept for elite sports. The authors` practical medical experience shows that up to 30% of elite athletes are diagnosed with musculoskeletal disorders normally associated with the sport-specific physical activity. The elite athletes not only strive to have cured the disorders and diseases but also maintain their health in the long-term remission phase to secure good physical shape and competitive accomplishments. To respond to these needs, the authors have designed and successfully tested and implemented an integrated rehabilitation concept for dorsopathy and periarthritis that includes the following four components: special physical exercises; special chondroprotectors administered as required by recommended procedure; special orthopedic appliances for quiescent and active service; and dynamic health control component. The spinal and articular disorders prevention concept was found beneficial as verified by its practical contributions to the professional sport longevity and compliance with the healthy lifestyle.